General statistics - Chase, Warren (John Wiley & Sons, 2000)
This text presents a complete first course in statistics appropriate for students enrolled in a wide variety of disciplines. This mainstream, mid-level text offers students, in a precise and accurate manner, the basic ideas of descriptive and inferential statistics.